2011
DOI: 10.1038/eye.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical impact and optical and morphological characteristics of symptomatic non-advanced cataract

Abstract: Purpose To investigate whether psychophysical, morphological, and/or optical characteristics of symptomatic non-advanced cataract are complementary to, or more appropriate than, visual acuity (VA) for the purposes of recording visual data that reflect subjective visual difficulty in patients with cataract that exhibit relative sparing of high contrast acuity (0.4 logarithm of minimal angle of resolution (logMAR) scale or better). Methods Eighty-two patients with symptomatic non-advanced cataract and no other o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…The construct validity of the VND-Q was supported in the present study, where respondents with poorer selfreported general vision in low-light and with glare had more vision-related night driving difficulties. Notably, respondents who self-reported bilateral eye conditions had more difficulties, which provides additional support of construct validity of the VND-Q, given that conditions such as glaucoma, 61 AMD 24,62 and cataract 63,64 are known to impair mesopic vision and increase glare sensitivity. However, the majority of respondents did not self-report any eye disease (69%), therefore the ability to generalise these results for glaucoma, AMD and cataract populations is limited.…”
Section: Discussionmentioning
confidence: 70%
“…The construct validity of the VND-Q was supported in the present study, where respondents with poorer selfreported general vision in low-light and with glare had more vision-related night driving difficulties. Notably, respondents who self-reported bilateral eye conditions had more difficulties, which provides additional support of construct validity of the VND-Q, given that conditions such as glaucoma, 61 AMD 24,62 and cataract 63,64 are known to impair mesopic vision and increase glare sensitivity. However, the majority of respondents did not self-report any eye disease (69%), therefore the ability to generalise these results for glaucoma, AMD and cataract populations is limited.…”
Section: Discussionmentioning
confidence: 70%
“…Pioneering studies has demonstrated that PBMs can be reliable and valid methods in assessing real-life visual ability. [13][14][15][16][17][18][19][20][21][22][23] Owing to its significance in visual hierarchy, PBMs of visual function is becoming an important part of researches on the real-life effects of visual diseases.…”
Section: Introductionmentioning
confidence: 99%
“…More recently there is a coming up of trend in developing a method for evaluation of functional vision-performance-based measures (PBMs) of visual function. [13][14][15][16][17][18][19][20][21][22][23] It involves presenting patients with commonly encountered tasks of daily life in a standardized format and getting a grade in accordance with their visual ability to complete the tasks. Pioneering studies has demonstrated that PBMs can be reliable and valid methods in assessing real-life visual ability.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,17 Based on the inherent limitations of clinical tests and self-report questionnaires, more recently there has been an upcoming interest in developing a complementary method for evaluation and outcome measures of visual function-the performancebased measures (PBMs) of visual function. 4,10,13,[18][19][20][21][22][23][24][25][26][27] Vision-specific PBMs take on actual performance of vision-related tasks. It involves presenting patients with commonly encountered tasks of daily life in a standardized format and getting a grade in accordance to their visual ability to complete the tests.…”
Section: Introductionmentioning
confidence: 99%